2015
DOI: 10.17507/tpls.0509.06
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Second Language Education

Abstract: Abstract-No doubt any discussion of language learning without taking into consideration the strong influence of social behavior will be in vain. Constructivist theories and methodologies of language learning have firmly refuted many key principles of cognitive theory which reckoned learners as individuals whose process of learning takes place in isolation. By putting accent on communication, the proponents of constructivism endeavor to bring into limelight the significant role the society and environment play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Spirituality in relation to different aspects of social experience, characteristic trait, cognition, and relationship is dynamically interwoven, created, and recreated into different levels of consciousness (Wilber, 2000). Therefore, spirituality could be referred to as a relative concept in terms of "connection with oneself, others, and the transcendent" (Galeh & Dorcheh, 2015, p.1810 as well as "freshness of perception" (Webster, 1996, p.249). Jones (2005) broadly defined spirituality as "our most authentic relationships to self, others, the universe, and the transcendent influence our personal health on all levels, the health of our communities, our nations, and the world" (p.1).…”
Section: Spirituality and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirituality in relation to different aspects of social experience, characteristic trait, cognition, and relationship is dynamically interwoven, created, and recreated into different levels of consciousness (Wilber, 2000). Therefore, spirituality could be referred to as a relative concept in terms of "connection with oneself, others, and the transcendent" (Galeh & Dorcheh, 2015, p.1810 as well as "freshness of perception" (Webster, 1996, p.249). Jones (2005) broadly defined spirituality as "our most authentic relationships to self, others, the universe, and the transcendent influence our personal health on all levels, the health of our communities, our nations, and the world" (p.1).…”
Section: Spirituality and Educationmentioning
confidence: 99%
“…Despite the significant role of philosophy in education especially for EFL/ESL teachers (Boone, Gartin, Buckingham, Odell & lawrence, 2001;Decoux, Rachal, Leonard & Pierce, 1992;Lehman, 2003;Spurgeon & Moore, 1994;Zandvanian, 2009) and the paucity of research on spirituality and language pedagogy (Bradley, 2011;Foster, 1997;Galeh & Dorcheh, 2015;Marler & Hadaway, 2002), further research on philosophical position and spiritual beliefs of EFL practitioners is necessitated. In the following section, the educational philosophies, and the role of spirituality in education are elaborated on.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the relationship between spirituality and language teaching remains interesting to explore. Galeh and Dorcheh revealed that the role of spirituality in language teaching as a catalyst for the learning process by increasing autonomy, self-confidence, and self-esteem (Galeh & Dorcheh, 2015). However, inquiries on the relationship between spirituality and English language learning still tend to be marginalised despite having a central role in everyday life, culture, and politics (Mahboob & Courtney, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To bridge the gap, they provided and sought out five broad questions that clarified how teachers’ spirituality can influence their professional practice. Likewise, Galeh and Dorcheh (2015) investigated the possible connection between language teaching and spirituality in Iran drawing on constructivist perspectives. After reviewing the literature, they found that pedagogy based on spirituality facilitates learning by enhancing sense of autonomy, self-confidence, empathy, self-esteem, and decreasing stress and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these promising studies, the impact of SP on L2 education is still insufficiently explored. ELT is a fertile ground for SP as English language is an international language ( Galeh and Dorcheh, 2015 ). Hence, L2 teachers and educators must take spirituality into account in order to establish modesty, humility, and worldviews among the stakeholders.…”
Section: Introductionmentioning
confidence: 99%